Avaliação nutricional da criança hospitalizada na Fundação Santa Casa de Misericórdia do Pará - COSTA, Mary Helly Valente (2022)
Introducion: Nutricional evalution is a valuable marker of a population health quality, pointing its development. It should be a part of a child health basic attention routine. Method: Observational, analytical and transversal study of 60 children with the age of 29 days old to 2 years old, hospitalized at the Santa Ludovina pediatrics’ward in FSCMPA, between the months of july to November of 2005. It was used the index weight/age, weight/stature, stature/age, express in score z with the variation of –6 to +6, signifying how many standard desviations (SD) the result is away of the mean reference. In nutritional classification was considered these: eutrophy z -1SD, mild malnutrition z-1 to – 1,9 SD, moderate malnutrition z -2 to – 2,9 SD, severe malnutrition z -3 SD. Results: Accord to stature/age index, it was found 28,3% of eutrofic children, 26,7% with mild malnutrition, 8,3% with moderate malnutrition and 31,7% with severe malnutrition. A deficit in stature/age index indicate that the child has a deficient grouth in a long time process. Accord to weight/stature index, 58,3% of children were eutrofics, 18,3% with mild malnutrition, 10% moderate malnutrition and 1,7% severe malnutrition. A deficit in weight/stature index, or a weight proporcionally below to expected to the stature found in a child, indicates a recente grouth diference that chipped in weight gain, but not yet in stature. For the weight/age index was found 35% eutrofics, 23,3% with mild malnutrition, 13,3% with moderate malnutrition and 21,7% with severe malnutrition. The weight/age index gives less information: its deficit on signify a recent or an old phenomenon Conclusions: The proposed approach takes into account the identification of all forms of malnutrition, from the mildest to the most severe cases, takes into consideration both height and weight deficits and if the process is acute or chronic. Therefore, it proveld a systeati device of many information.